Insulating substrate and method for manufacturing the same

CN122879544APending Publication Date: 2026-10-09MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611204114.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0012]然而,在专利文献1中,通过规定S的含量来抑制晶粒的粗大化,但即便仅规定S的含量,也无法得到充分的晶粒粗大化抑制效果

Benefits of technology

[0027]根据本发明,能够提供一种即使在加热后也能够抑制晶粒的粗大化及不均匀化的铜材及由该铜材构成的散热部件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879544A_ABST
    Figure CN122879544A_ABST
Patent Text Reader

Abstract

Provided is an insulating substrate capable of suppressing coarsening and unevenness of crystal grains even after heating, and a manufacturing method thereof. The insulating substrate of the present invention includes a ceramic substrate and a copper material joined to the ceramic substrate, the copper material having a composition containing Ca in a range of 3 mass ppm or more and 400 mass ppm or less and the remainder being Cu and inevitable impurities, wherein, when the content of Ca is set as X (mass ppm) and the total content of O, S, Se, and Te contained as the inevitable impurities is set as Y (mass ppm), X / Y > 2, and, with respect to the copper material before being joined to the ceramic substrate, after heat treatment at 800°C for 1 hour, the average crystal grain size is 200 μm or less, and the area ratio of crystal grains in a range of 50 μm or more and 300 μm or less in grain size is 60% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application filed on March 9, 2020, with application number 202080024700.8 and invention title "Copper Material and Heat Dissipation Components". Technical Field

[0002] This invention relates to a copper material and heat dissipation component suitable for electrical and electronic parts such as heat sinks or thick copper circuits, and more particularly to a copper material and heat dissipation component that can suppress grain coarsening during heating.

[0003] This application claims priority based on Japanese Patent Application No. 2019-068349, filed on March 29, 2019, the contents of which are incorporated herein by reference. Background Technology

[0004] In the past, highly conductive copper or copper alloys were used in electrical and electronic components such as heat sinks or thick copper circuits.

[0005] Recently, with the increasing current in electronic and electrical equipment, efforts are being made to increase the size and thickness of electrical and electronic components used in these devices in order to reduce current density and dissipate heat generated by Joule heating.

[0006] In semiconductor devices, insulating circuit boards, for example, are used to form the aforementioned heat sinks or thick copper circuits by bonding copper material onto a ceramic substrate.

[0007] When ceramic substrates are bonded to copper plates, the bonding temperature is mostly above 800°C, which may cause the grains of the copper material constituting the heat sink or thick copper circuit to coarsen during bonding. In particular, there is a tendency for grain coarsening in copper materials composed of pure copper, which has particularly excellent conductivity and heat dissipation.

[0008] When the grains become coarse in the heat sink or thick copper circuit after bonding, appearance problems may occur due to the coarsening of the grains.

[0009] Therefore, for example, Patent Document 1 proposes a copper material intended to suppress grain growth when heated to high temperatures.

[0010] Patent document 1 describes the following: by containing 0.0006 to 0.0015% by weight of S, even if heat treatment is performed above the recrystallization temperature, the grains can still be adjusted to a certain size.

[0011] Patent Document 1: Japanese Patent Application Publication No. 06-002058

[0012] However, in Patent Document 1, the coarsening of grains is suppressed by specifying the content of sulfur (S), but even specifying only the content of S cannot achieve a sufficient effect in suppressing grain coarsening. Furthermore, there is a situation where localized grain coarsening occurs after heating, resulting in an uneven crystalline structure.

[0013] Furthermore, in order to suppress grain coarsening, the sulfur content is increased, but the hot workability is greatly reduced, which will result in a significant decrease in the yield of copper products. Summary of the Invention

[0014] The present invention was made in view of the foregoing circumstances, and its object is to provide a copper material and a heat dissipation component made of the copper material that can suppress grain coarsening and non-uniformity even after heating.

[0015] In order to solve this problem, the inventors conducted in-depth research and obtained the following insights.

[0016] When copper is heated after plastic processing, strain is released through primary recrystallization at a low temperature, resulting in a homogeneous structure. However, secondary recrystallization at a high temperature (e.g., above 800°C) causes some grains to coarsen, resulting in a non-homogeneous structure. Therefore, by suppressing secondary recrystallization at a high temperature, grain coarsening and non-homogenization can be suppressed.

[0017] Furthermore, in copper materials with an appropriate amount of Ca, Ca reacts with S, Se, and Te, which are unavoidable impurities, to form compounds (hereinafter referred to as Ca-based compounds). A portion of these Ca-based compounds decomposes at temperatures above 800°C, and Ca, S, Se, and Te dissolve in the parent phase. Grain growth can be suppressed by these Ca, S, Se, and Te.

[0018] The present invention was made based on the above-mentioned insights. The copper material of the present invention is characterized in that its composition is such that the content of Ca is in the range of 3 ppm by mass and 400 ppm by mass, and the remainder is Cu and unavoidable impurities. When the content of Ca is set as X (ppm by mass) and the total content of O, S, Se and Te contained as the unavoidable impurities is set as Y (ppm by mass), X / Y > 2. After heat treatment at 800°C for 1 hour, the average crystal grain size A is 200 μm or less, and the area ratio of grains with a grain size of 50 μm or more and 300 μm or less is 60% or more.

[0019] In this copper material, the Ca content is between 3 ppm and 400 ppm by mass. During casting, Ca reacts with S, Se, and Te, which are unavoidable impurities, to form Ca-based compounds. When these Ca-based compounds are heated at high temperatures, they decompose into Ca, S, Se, and Te, which dissolve in the parent phase. The dissolved Ca, S, Se, and Te hinder grain growth. Therefore, secondary recrystallization caused at high temperatures (e.g., above 800°C) can be effectively suppressed, and grain coarsening and inhomogeneity can also be suppressed after heating.

[0020] Furthermore, since X / Y > 2 when the content of Ca is set as X (mass ppm) and the total content of O, S, Se and Te, which are unavoidable impurities, is set as Y (mass ppm), even if Ca is preferentially oxidized and consumed, it is possible to ensure that Ca reacts with S, Se and Te, thereby fully generating Ca-based compounds.

[0021] Furthermore, since the average crystal grain size A is less than 200 μm after heat treatment at 800 °C for 1 hour, and the area ratio of grains with a grain size of 50 μm or more and less than 300 μm is more than 60%, grain coarsening and inhomogeneity can be reliably suppressed even when heated to 800 °C or more.

[0022] Here, in the copper material of the present invention, it is preferable that when the average crystal grain size after heat treatment at 800°C for 1 hour is set as A, and the average crystal grain size after heat treatment at 1000°C for 1 hour is set as B, B / A≤2.

[0023] In this case, the difference between the average crystal grain size B after heat treatment at 1000°C for 1 hour and the average crystal grain size A after heat treatment at 800°C for 1 hour is small. Even when heated to a high temperature, the coarsening and inhomogeneity of the grains can be effectively suppressed.

[0024] Furthermore, in the copper material of the present invention, it is preferable that the unavoidable impurities other than O, S, Se and Te mentioned above are 0.1% by mass or less in total.

[0025] The heat dissipation component of the present invention is characterized in that it is made of the aforementioned copper material.

[0026] The heat dissipation component with this structure is made of the aforementioned copper material, so even when heated to a high temperature of over 800°C during bonding, it can suppress grain coarsening and non-uniformity.

[0027] According to the present invention, a copper material and a heat dissipation component made of the copper material can be provided that can suppress grain coarsening and non-uniformity even after heating. Attached Figure Description

[0028] Figure 1 This is a flowchart of the copper material manufacturing method according to this embodiment. Detailed Implementation

[0029] The copper material according to one embodiment of the present invention will be described below.

[0030] The copper material in this embodiment can be used as a material for electrical and electronic components such as heat sinks or thick copper circuits, and is used, for example, when forming the electrical and electronic components, by bonding them with a ceramic substrate.

[0031] The copper material composition of this embodiment is such that the Ca content is in the range of 3 ppm by mass and 400 ppm by mass, and the remainder is Cu and unavoidable impurities. When the Ca content is set as X (ppm by mass) and the total content of O, S, Se and Te contained as unavoidable impurities is set as Y (ppm by mass), the relationship X / Y>2 is satisfied.

[0032] Furthermore, in the copper material of this embodiment, after heat treatment at 800°C for 1 hour, the area ratio of grains with an average crystal grain size A of 200 μm or less and a grain size of 50 μm or more and 300 μm or less is 60% or more.

[0033] Furthermore, in the copper material of this embodiment, it is preferable that when the average crystal grain size after heat treatment at 800°C for 1 hour is set as A, and the average crystal grain size after heat treatment at 1000°C for 1 hour is set as B, B / A≤2.

[0034] Furthermore, in the copper material of this embodiment, unavoidable impurities other than O, S, Se and Te are less than 0.1% by mass in total.

[0035] Here, the reasons for specifying the composition and average grain size after heat treatment in the copper material of this embodiment will be explained below.

[0036] (Ca content: above 3 ppm by mass and below 400 ppm by mass)

[0037] Ca reacts with S, Se, and Te, which are unavoidable impurities, to form Ca-based compounds. A portion of these compounds decomposes at high temperatures, and Ca dissolves in S, Se, and Te. Therefore, the growth of grains can be suppressed by the dissolved Ca, S, Se, and Te.

[0038] Here, when the Ca content is below 3 ppm by mass, Ca-based compounds may not be sufficiently formed. On the other hand, when the Ca content exceeds 400 ppm by mass, coarse Ca-based compounds are formed, which may significantly reduce processability.

[0039] Therefore, in this embodiment, the content of Ca is set in the range of 3 ppm by mass or more and 400 ppm by mass or less.

[0040] Furthermore, the Ca content is preferably 3.5 ppm by mass or more, more preferably 4 ppm by mass or more. The Ca content is preferably 350 ppm by mass or less, more preferably 300 ppm by mass or less, and more preferably 100 ppm by mass or less.

[0041] (The ratio of Ca content X to the total content Y of O, S, Se and Te: X / Y > 2)

[0042] Compared with S, Se, and Te, Ca has a higher reactivity with O and is preferentially oxidized and consumed.

[0043] Therefore, by ensuring that the ratio X / Y of the Ca content X to the total content Y of O, S, Se and Te, which are unavoidable impurities, is greater than 2, the amount of Ca remaining after Ca is consumed through oxidation can be sufficiently ensured. Through the reaction of S, Se and Te with the remaining Ca, Ca-based compounds can be fully generated.

[0044] Furthermore, the ratio of Ca content X to the total content Y of O, S, Se, and Te, X / Y, is preferably 2.2 or higher, and more preferably 2.5 or higher. There is no particular upper limit to the X / Y ratio, but it is practically 50 or lower.

[0045] (Other unavoidable impurities)

[0046] Other unavoidable impurities besides the elements mentioned above include: Ag, B, Bi, Sc, rare earth elements (except Sc and Y), V, Nb, Ta, Cr, Mg, Sr, Ba, Ti, Zr, Hf, Y, Mo, W, Mn, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pb, Pd, Pt, Au, Zn, Cd, Hg, Al, Ga, In, Ge, Sn, As, Sb, Tl, Be, N, C, Si, Li, and H. Since these unavoidable impurities may reduce thermal conductivity, they are preferably present in amounts of 0.1% by mass or less.

[0047] (The average crystal grain size A after heat treatment at 800℃ for 1 hour is less than 200μm)

[0048] In the copper material of this embodiment, when the average crystal grain size is less than 200 μm after heat treatment at 800°C for 1 hour, grain coarsening can be reliably suppressed even when heated to above 800°C.

[0049] Furthermore, the average crystal grain size after heat treatment at 800°C for 1 hour is preferably 180 μm or less, more preferably 150 μm or less. While there is no particular limitation on the lower limit of the average crystal grain size after heat treatment at 800°C for 1 hour, it is substantially 50 μm or more.

[0050] (The area ratio of grains with a particle size of 50μm or larger and 300μm or smaller after heat treatment at 800℃ for 1 hour is 60% or more.)

[0051] In the copper material of this embodiment, when the area ratio of grains with a particle size of 50 μm or more and 300 μm or less is 60% or more after heat treatment at 800°C or higher, grain inhomogeneity can be reliably suppressed even when heated to 800°C or higher.

[0052] Furthermore, the minimum particle size falling within the range of 60% or more of the area of ​​the grains after heat treatment at 800°C for 1 hour is preferably 75 μm or more, and more preferably 100 μm or more.

[0053] (The ratio of the average crystal grain size A after heat treatment at 800℃ for 1 hour to the average crystal grain size B after heat treatment at 1000℃ for 1 hour: B / A≤2)

[0054] In the copper material of this embodiment, when the ratio B / A of the average grain size A after heat treatment at 800°C for 1 hour to the average grain size B after heat treatment at 1000°C for 1 hour is less than 2, the difference between the average grain size B after heat treatment at 1000°C for 1 hour and the average grain size A after heat treatment at 800°C for 1 hour is small, and even when heated to a high temperature, grain coarsening and non-uniformity can be sufficiently suppressed.

[0055] Furthermore, the ratio B / A of the average crystal grain size A after heat treatment at 800°C for 1 hour to the average crystal grain size B after heat treatment at 1000°C for 1 hour is preferably 1.9 or less, more preferably 1.5 or less. While there is no particular limitation on the lower limit of B / A, it is substantially 0.8 or more.

[0056] Next, regarding the method for manufacturing the copper material of this embodiment, which is configured as described above, refer to... Figure 1 The flowchart shown is used for illustration.

[0057] (S01: Melting and casting process)

[0058] First, copper raw materials are melted to produce molten copper. Additionally, oxygen-free copper with a purity of 99.99% by mass or higher, and oxygen-free copper with a purity of 99.999% by mass or higher, are preferably used as the copper raw materials.

[0059] Next, Ca is added to the obtained copper molten liquid to achieve a specified concentration for composition modulation. Furthermore, Ca monomers or Cu-Ca master alloys can be used when adding Ca. Moreover, when manufacturing the Cu-Ca master alloy, oxygen-free copper with a purity of 99.99% by mass or higher, and oxygen-free copper with a purity of 99.999% by mass or higher, are preferably used.

[0060] Furthermore, the copper molten liquid with adjusted composition is poured into a mold to produce an ingot. In addition, considering mass production, continuous casting or semi-continuous casting is preferred.

[0061] During the melting and casting process S01, a portion of the added Ca reacts with S, Se, and Te, which are unavoidable impurities, to generate Ca-based compounds.

[0062] (Hot working process S02)

[0063] Next, heat treatment is performed to homogenize the structure. The heating in this heat treatment step is preferably carried out in a non-oxidizing or reducing atmosphere.

[0064] There are no particular restrictions on the hot working temperature, but it is preferably in the range of 500°C or higher and 1000°C or lower. In subsequent processes, in order to uniformly generate Ca-based compounds and taking into account the heat generated during processing, the starting temperature for hot working is preferably 700°C or higher. More preferably, it is 750°C or higher.

[0065] Furthermore, the total processing rate of the hot working is preferably 40% or more, more preferably 60% or more, and even more preferably 70% or more.

[0066] The final temperature of the heat treatment is preferably below 700°C. More preferably, it is below 650°C.

[0067] In addition, there are no particular restrictions on the cooling method after hot processing, but air cooling or water cooling is preferred.

[0068] Furthermore, there are no particular limitations on the processing method in the hot working process S02. For example, rolling, extrusion, groove rolling, forging, and pressurization can be used. When the final shape is a plate or strip, rolling is preferred; when the final shape is a wire or bar, extrusion or groove rolling is preferred; and when the final shape is a block, forging or pressurization is preferred.

[0069] (Cold processing step S03)

[0070] Next, the copper material after the hot working step S02 is cold-worked to form a predetermined shape. Furthermore, the temperature conditions in this cold working step S03 are not particularly limited, but are preferably performed in a range of -200°C to 200°C. The processing rate in this cold working step S03 is appropriately selected to approximate the final shape, but to improve productivity, it is preferably 30% or higher.

[0071] Furthermore, the processing method in the cold working step S03 is not particularly limited; for example, rolling, extrusion, groove rolling, forging, and pressurization can be used. When the final shape is a plate or strip, rolling is preferred; when the final shape is a wire or bar, extrusion or groove rolling is preferred; and when the final shape is a block, forging or pressurization is preferred.

[0072] (Recrystallization heat treatment process S04)

[0073] Next, the copper material after the cold working step S03 undergoes a heat treatment for recrystallization. Here, if the recrystallized grains are fine after the recrystallization heat treatment step S04, subsequent heating to 800°C or higher may promote grain growth and lead to microstructure inhomogeneity. Therefore, it is preferable to set the average grain size of the recrystallized grains after the recrystallization heat treatment step S04 to 10 μm or more. More preferably, it is 15 μm or more, and even more preferably, it is 20 μm or more. There is no specific upper limit for the grain size during recrystallization, but it is substantially 200 μm or less.

[0074] The heat treatment conditions for the recrystallization heat treatment step S04 are not particularly limited, but it is preferable to maintain a heat treatment temperature in the range of 200°C to 850°C for a period of 1 second to 24 hours. In this case, in order to ensure that the particle size after recrystallization falls within the above-mentioned range, it is preferable to perform heat treatment at a high temperature for a short time and heat treatment at a low temperature for a long time. The cooling rate is not particularly specified, but when heat treatment is performed at a temperature of 800°C or higher, the cooling rate at a temperature of 500°C to 800°C is preferably 10°C / second or lower, and more preferably 5°C / second or lower, and even more preferably 1°C / second or lower.

[0075] Furthermore, in order to homogenize the recrystallized structure, the cold working process S03 and the recrystallization heat treatment process S04 can be repeated more than twice.

[0076] (Tempering and conditioning process S05)

[0077] Next, in order to adjust the material strength, the copper material after the recrystallization heat treatment process S04 can also be subjected to quenching and tempering. Alternatively, if it is not necessary to improve the material strength, quenching and tempering can be omitted.

[0078] There is no particular limitation on the processing rate of quenching and tempering, but it is preferable to carry it out in the range of more than 0% and less than 50% in order to adjust the material strength. Furthermore, if necessary, heat treatment can be performed after quenching and tempering to remove residual strain.

[0079] In this way, the copper material of this embodiment can be produced.

[0080] In the copper material of this embodiment configured as described above, since the Ca content is in the range of 3 ppm by mass or more and 400 ppm by mass or less, during casting, hot working, and recrystallization heat treatment, Ca reacts with S, Se, and Te, which are unavoidable impurities, to form Ca-based compounds. When these Ca-based compounds are heated to 800°C or higher, they decompose into Ca, S, Se, and Te and dissolve in solid solution. The dissolved Ca, S, Se, and Te hinder grain growth. Therefore, even when the copper material is heated to, for example, 800°C or higher, secondary recrystallization can be sufficiently suppressed, and grain coarsening and inhomogeneity can be suppressed after heating.

[0081] Furthermore, in the copper material of this embodiment, since the ratio X / Y of the Ca content X (mass ppm) to the total content Y (mass ppm) of O, S, Se and Te contained as unavoidable impurities is set to be greater than 2, even if Ca is consumed by preferentially reacting with oxygen, the amount of residual Ca that reacts with S, Se and Te can be ensured, thereby enabling the sufficient generation of Ca-based compounds.

[0082] Furthermore, in the copper material of this embodiment, since the average grain size (A) is less than 200 μm after heat treatment at 800°C for 1 hour, grain coarsening can be reliably suppressed even when the copper material is heated to 800°C or higher.

[0083] Furthermore, in the copper material of this embodiment, since the area ratio of grains with a particle size of 50 μm or more and 300 μm or less is 60% or more after heat treatment at 800°C for 1 hour, even when the copper material is heated to 800°C or more, grain inhomogeneity can be reliably suppressed.

[0084] Furthermore, in the copper material of this embodiment, when the ratio B / A of the average grain size A after heat treatment at 800°C for 1 hour to the average grain size B after heat treatment at 1000°C for 1 hour is less than 2, the difference between the average grain size B after heat treatment at 1000°C for 1 hour and the average grain size A after heat treatment at 800°C for 1 hour is small, and even when heated to a high temperature of 1000°C or higher, grain coarsening and non-uniformity can be sufficiently suppressed.

[0085] The copper material of the embodiments of the present invention has been described above, but the present invention is not limited thereto, and appropriate changes can be made without departing from the technical concept of the present invention.

[0086] For example, in the above embodiments, an example of a method for manufacturing copper material has been described, but the method for manufacturing copper material is not limited to the method described in the embodiments, and existing manufacturing methods may also be appropriately selected.

[0087] Example

[0088] The results of the confirmation experiments conducted to verify the effectiveness of the present invention will be described below.

[0089] Copper raw material consisting of oxygen-free copper with a purity of 99.99% by mass or higher was placed in a high-purity graphite crucible and subjected to high-frequency melting in an atmosphere furnace set with Ar gas. A Cu-1% by mass Ca master alloy was then added to the resulting molten copper to prepare the composition shown in Table 1.

[0090] The obtained molten copper is poured into a mold to produce an ingot. The ingot is approximately 25 mm thick, 70 mm wide, and 160–190 mm long.

[0091] The resulting ingot was heated at 800°C for 1 hour in an Ar gas atmosphere and then hot rolled to a thickness of 15 mm.

[0092] The hot-rolled copper material was cut off, and surface grinding was performed to remove the oxide film on the surface. At this point, taking into account the rolling rate of subsequent cold rolling and temper rolling, the thickness of the copper material supplied for cold rolling was adjusted to a final thickness of 0.8 mm.

[0093] For copper materials with adjusted thickness as described above, cold rolling was performed at a processing rate of 90%.

[0094] Next, the cold-rolled copper material was subjected to recrystallization heat treatment at 600–850°C for 5 seconds.

[0095] Furthermore, copper materials that have undergone recrystallization heat treatment were subjected to temper rolling at a processing rate of 5-50% to produce copper materials with a thickness of 0.8 mm and a width of 60 mm.

[0096] Furthermore, the following items were evaluated. The evaluation results are shown in Table 2.

[0097] (Composition analysis of copper materials)

[0098] Samples were collected from the obtained copper material and their composition was analyzed using an ICP-MS apparatus (AGILENT 7500CX). The results confirmed the composition shown in Table 1.

[0099] (Average crystal grain size A after heat treatment at 800℃ for 1 hour)

[0100] The obtained copper material was subjected to a heat treatment at 800°C for 1 hour. Samples measuring 50mm x 50mm were cut from the test piece, mechanically polished with water-resistant sandpaper or diamond abrasive, and then finely polished with a colloidal silica solution.

[0101] The EBSD measurement device (FEI QUANTA 450 EFG, EDAX / TSL AMETEK 9424) and analysis software (TSL OIM Analysis 7×64) were used to measure the results in 5 μm increments at 1000 μm intervals. 2 Within the measured area, measurement points with an orientation difference of 15° or more between adjacent measurement points are considered grain boundaries, and a grain boundary mapping map is constructed. Measurement points with a CI value below 0.1 are removed when constructing the grain boundary mapping map.

[0102] According to the cutting method of JIS H 0501, for the above grain boundary mapping diagram, five line segments of specified length are drawn along the longitudinal and transverse directions. The number of grains that are completely cut off by the line segments is counted, and the average value of the cut length is set as the average crystal grain size.

[0103] (The area ratio of grains with a diameter of 50 μm or more and 300 μm or less after heat treatment at 800℃ for 1 hour)

[0104] From the grain boundary map prepared when the average grain size A was measured above, the grain size of each grain was determined using analysis software (TSL OIM Analysis 7×64). Using the area fraction, the area ratio of grains with a grain size of 50 μm or more and 300 μm or less was calculated from the total area of ​​all grains.

[0105] (Average crystal grain size B after heat treatment at 1000℃ for 1 hour)

[0106] Test pieces were taken from the obtained copper material and subjected to heat treatment at 1000℃ for 1 hour. From the test pieces, 50mm×50mm samples were cut out, and the average crystal grain size B after heat treatment at 1000℃ for 1 hour was calculated by following the same steps as described above for "average crystal grain size A after heat treatment at 800℃ for 1 hour".

[0107] [Table 1]

[0108]

[0109] [Table 2]

[0110]

[0111] In Comparative Example 1, without the addition of Ca, the average grain size A after heat treatment at 800°C for 1 hour was 215 μm, and the average grain size B after heat treatment at 1000°C for 1 hour was 478 μm, indicating grain coarsening after heat treatment. Furthermore, the area fraction of grains with a grain size of 50 μm or larger and 300 μm or smaller after heat treatment at 800°C for 1 hour was low at 55%, indicating non-uniform grain structure after heat treatment.

[0112] In Comparative Example 2, the ratio of Ca content X (mass ppm) to the total content Y (mass ppm) of O, S, Se, and Te (which are unavoidable impurities) was 0.2. The average grain size A after heat treatment at 800°C for 1 hour was 204 μm, and the average grain size B after heat treatment at 1000°C for 1 hour was 506 μm, indicating grain coarsening after heat treatment. Furthermore, the area fraction of grains with a size of 50 μm or more and 300 μm or less after heat treatment at 800°C for 1 hour was low at 49%, indicating non-uniform grain structure after heat treatment.

[0113] In Comparative Example 3, the ratio of Ca content X (mass ppm) to the total content Y (mass ppm) of O, S, Se, and Te (which are unavoidable impurities) was 1.5. The average grain size A after heat treatment at 800°C for 1 hour was 233 μm, and the average grain size B after heat treatment at 1000°C for 1 hour was 557 μm, indicating grain coarsening after heat treatment. Furthermore, the area fraction of grains with a size between 50 μm and 300 μm after heat treatment at 800°C for 1 hour was low at 51%, indicating non-uniform grain structure after heat treatment.

[0114] In Comparative Example 4, the Ca content was 543 ppm by mass, and fracture occurred during processing. Therefore, subsequent evaluation was discontinued. It is speculated that this was due to the formation of coarse Ca-based compounds during casting.

[0115] In this regard, in Examples 1-15 of the present invention, where the Ca content is in the range of 3 ppm to 400 ppm by mass, and the remainder is Cu and unavoidable impurities, and the ratio X / Y of the total content Y of O, S, Se, and Te (which are unavoidable impurities) is greater than 2, the average grain size A after heat treatment at 800°C for 1 hour is 155 μm or less, and the average grain size B after heat treatment at 1000°C for 1 hour is 183 μm or less, thus suppressing grain coarsening after heat treatment. Furthermore, the area ratio of grains with a grain size of 50 μm or more and 300 μm or less after heat treatment at 800°C for 1 hour is 60% or more, indicating uniform grain size after heat treatment.

[0116] As can be seen from the above, according to the present invention, it has been confirmed that a copper material can be provided that can suppress grain coarsening and inhomogeneity even after heating.

[0117] Industrial availability

[0118] The copper material and heat dissipation component of the present invention are suitable for use in components that preferably suppress grain coarsening to prevent changes in appearance, such as electrical and electronic components with heat sinks or thick copper circuits.

Claims

1. An insulating substrate, characterized in that, have: Ceramic substrate; and Copper material bonded to the ceramic substrate. The copper material has a composition containing Ca in the range of 3 ppm by mass and 400 ppm by mass, with the remainder being Cu and unavoidable impurities. In the copper material, when the content of Ca is set as X, and the total content of O, S, Se, and Te, which are unavoidable impurities, is set as Y, X / Y > 2, wherein the units of the Ca content and the total content are in ppm by mass. Regarding the copper material before bonding with the ceramic substrate, after heat treatment at 800°C for 1 hour, the area ratio of grains with an average crystal grain size of 200 μm or less and a grain size range of 50 μm or more and 300 μm or less is 60% or more.

2. The insulating substrate according to claim 1, characterized in that, Regarding the copper material before bonding with the ceramic substrate, if the average grain size after heat treatment at 800°C for 1 hour is set as A, and the average grain size after heat treatment at 1000°C for 1 hour is set as B, then B / A≤2.

3. The insulating substrate according to claim 1, characterized in that, The unavoidable impurities, other than O, S, Se and Te, are less than 0.1% by mass in total.

4. The insulating substrate according to claim 1, characterized in that, The copper material is a heat dissipation component.

5. A method for manufacturing an insulating substrate, characterized in that, The manufacturing method is the method for manufacturing the insulating substrate according to any one of claims 1 to 4, comprising: The process of manufacturing copper materials by heat treatment for recrystallization, which involves casting copper raw materials with added Ca and then performing hot and cold working; and The process of bonding the manufactured copper material to a ceramic substrate.

Citation Information

Patent Citations

  • Crystal grain growth suppressing oxygen free copper

    JP1994002058A

  • Information processing system, information processing apparatus, information processing method, and information processing program

    JP2019068349A